In praise of discrepancy? Art and ideology revisited. (1st September 2014) - Bosteels, Bruno
This article traces a brief genealogy of the move from totality to discrepancy as a major shift in the understanding of ideology and its critique as it supposedly takes place in art. Drawing on the work of Jorge Luis Borges, a model is developed for the study of 'theoretical ideology', as distinct both from the 'political ideology' of the author and from the 'aesthetic ideology' of his work. Borges's texts on the paradox of Achilles and the tortoise, in particular, are read as signposts on the path that leads from Lukács to Adorno and from Sartre to Lacan or Miller.